Rancang Bangun Aplikasi Jam Tangan Pranata Laboratorium Pendidikan dengan Kemampuan Waterpas Tiga Dimensi untuk Mengatur Sambungan Modul Uji Pembebanan Motor - Mochammad Darwis; Aris Eko Saputro (UPT Laboratorium Terpadu, Universitas Diponegoro, 2020)
When testing the loading of an electric machine, we often experience problems in finding a tool to see the precision of the connection between the shaft of an electric machine. Shaft connections that are not straight and not right in the middle can damage the shaft of the rotating engine and the engine being rotated. This research is the development of previous research that uses Android phone as a tool. By reading the value of the orientation sensor on an android phone, we can measure the angle of rotation on the x, y and z axes. The Watpasdroid application will display the value on each axis. This application has also been used in the Electric Driving Laboratory at the Surabaya State Electronic Polytechnic (PENS), to check the connection (coupling) between an electric motor and a magnetic load (dynamo meter). The size of a cellphone that is still too large is sometimes become a problem if the surface being measured is narrow. So we uses a wristband-shaped watch module that already has a gyro sensor and can be programmed according to our need. The size is almost 1/12 of ordinary cellphones. The M5Stick-C module is used to compare the gyro reading value displayed by the wristband. To test the quality of motor joint which flatness checks have been assisted by using a wristband, a thermal observation camera is used. This application, does not rule out, can be used in other laboratories for the purpose of checking the plane levelness or equality in two dimensions or three dimensions.